Antifungal Prophylaxis in Solid Organ Transplant Recipients - Şebnem ŞENOL; Oya Eren KUTSOYLU; Onur KAYA; Meltem AVCI; Meltem IŞIKGÖZ TAŞBAKAN; Vildan AVKAN OĞUZ; Betil Özhak BAYSAN; Sema Alp ÇAVUŞ; Çiğdem Banu ÇETİN; Çağrı ERGİN; Bülent ERTUĞRUL; Selda SAYIN KUTLU; et al. (Mediterranean Journal of Infection, Microbes and Antimicrobials, 2015)
Solid organ transplantation (SOT) is a treatment method that improves quality of life and survival of patients with end-stage organ failure. Immunosuppressive treatments given to these patients may predispose to the development of invasive fungal infections (IFI). The incidence of IFI in SOT recipients, which is between 5% and 42%, depends on the organ to be transplanted. Although Candida spp., followed by Aspergillus spp. are the most common microorganisms, among fungal pathogens, this situation varies according to transplant type. The mortality rate associated with these IFI can be high. Therefore, antifungal prophylaxis may be necessary for SOT recipients. Many transplantation centers employ antifungal strategies according to their own experience because of the lack of randomized controlled studies. If the antifungal prophylaxis is given to all patients, antimicrobial resistance and drug-drug interactions may occur. Therefore, it is important to identify patients at a high risk of developing IFI. In this paper, epidemiology, risk factors, literature data and antifungal prophylaxis associated with IFI in liver, kidney, small intestine, pancreas, heart, and lung transplant recipients are reviewed.